Smart Multifunctional Nanoparticles in Cancer Theranostics: Progress and Prospect - Karati, Dipanjan; Mukherjee, Swarupananda; Dutta, Ayon; Ash, Dipanjana; Ganguly, Shayeri Chatterjee; Acharya, Apurbaa; Basu, Biswajit (Pharmaceutical Nanotechnology, 2025)
BackgroundWorldwide, cancer is the second most common cause of death. Chemotherapy and other traditional cancer treatments have toxicities that affect normal cells in addition to their intended targets, necessitating the development of novel approaches to enhance cell-specific targeting.MethodsThe present work summarizes the scientific information on nanoparticles in cancer theranostics to provide a comprehensive insight into the preventive and therapeutic potential of nanoparticles in cancer. Scopus, PubMed, Science Direct, and Google Scholar databases are searched to collect all the recent (2015-2023) scientific information on smart multifunctional nanoparticles using the terms nanotechnology, cancer theranostics, and polymer.ResultsThe use of nanomaterials as chemical biology tools in cancer theranostics has been thoroughly investigated. They demonstrate expanded uses in terms of stability, biocompatibility, and enhanced cell permeability, enabling precision targeting and ameliorating the drawbacks of conventional cancer treatments. The nano platform presents a fascinating chance to acquire multifunctionality and targeting techniques. The production of smart nanomaterials, specifically with regard to the advent of nanotechnology, has revolutionized the diagnosis and treatment of cancer. The capability of nanoparticles to functionalize with a variety of biosubstrates, including aptamers, antibodies, DNA, and RNA, and their broad surface area allow them to encapsulate a huge number of molecules, contributing to their theranostic effect. Comparatively speaking, economical, easily produced, and less toxic nanomaterials formed from biological sources are thought to have benefits over those made using conventional processes.ConclusionThe present study highlights the uses of several nanoparticles (NPs), and describes numerous cancer theranostics methodologies. The benefits and difficulties preventing their adoption in cancer treatment and diagnostic applications are also critically reviewed. The use of smart nanomaterials, according to this review's findings, can considerably advance cancer theranostics and open up new avenues for tumor detection and treatment.
Keywords: polymer